Ovarian Teratoma with Torsion Masquerading as Intussusception in 4-Year-Old Child - Smith, Carl J. (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2008)
BACKGROUND: Ovarian torsion (OT) occurs primarily in women of child-bearing age, but is rare in the pediatric population. The clinical presentation often consists of nonspecific abdominal complaints making the diagnosis difficult. Radiologic and sonographic evidence can be misleading. Although the delay in diagnosis from symptom onset is common, rapid diagnosis of ovarian torsion is imperative to prevent morbidity. CASE REPORT: We present the case of a four-year-old female who presented to the emergency department (ED) with a five-day history of intermittent abdominal pain and emesis. Initial diagnosis was suspicious for intussusception; however, on operative exploration, she was found to have a right adnexal torsion secondary to an ovarian teratoma. A right salpingo-oophorectomy was performed. CONCLUSION: Early diagnosis of ovarian torsion may increase ovarian salvage and reduce morbidity. Faced with abdominal pain of uncertain etiology in a female child, emergency physicians should include ovarian torsion secondary to an ovarian mass in the differential diagnosis.